2017
DOI: 10.1111/bph.13834
|View full text |Cite
|
Sign up to set email alerts
|

A critical assessment of the synthesis and biological activity of p53/human double minute 2‐stapled peptide inhibitors

Abstract: Cytosolic and nuclear accumulation was not an intrinsic property of the stapled peptide, but resulted from capture by the target Hdm2 after endo-lysosomal release. Considering the rather poor uptake of stapled peptides, further development should focus on increasing the efficiency of uptake of these peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
1
16
1
4
Order By: Relevance
“…[108] Brock and coworkers showed that as eries of hydrocarbon-stapled Hdm2binding peptides were taken up similarly to their linear precursors. [125] Clearly,h elical structure does not guarantee efficient uptake.I nstead, the predominance of helical structures among cell-penetrant stapled peptides may reflect the intrinsic ability of a-helices to present amphipathic character and al arge,c ontinuous hydrophobic surface,w hich are required for efficient uptake. [126] Fore xample,arecent screen for cell-penetrant variants of an autophagy-inducing peptide was not biased for any specific secondary structure, yet it discovered ac ell-penetrant a-helix with an unusual staple configuration.…”
Section: Amphipathic Patterning Canp Romote Endocytic Uptake For Consmentioning
confidence: 99%
“…[108] Brock and coworkers showed that as eries of hydrocarbon-stapled Hdm2binding peptides were taken up similarly to their linear precursors. [125] Clearly,h elical structure does not guarantee efficient uptake.I nstead, the predominance of helical structures among cell-penetrant stapled peptides may reflect the intrinsic ability of a-helices to present amphipathic character and al arge,c ontinuous hydrophobic surface,w hich are required for efficient uptake. [126] Fore xample,arecent screen for cell-penetrant variants of an autophagy-inducing peptide was not biased for any specific secondary structure, yet it discovered ac ell-penetrant a-helix with an unusual staple configuration.…”
Section: Amphipathic Patterning Canp Romote Endocytic Uptake For Consmentioning
confidence: 99%
“…[172,173] Bei CAPA werden Zellen zunächst mit dem zu untersuchenden, Chloralkan-markierten Molekülg epulst, das bei Erreichen des Zytosols HaloTag kovalent blockiert. [125,[179][180][181][182] Die Entscheidung, wie ein Peptid zu modifizieren ist, um es intrinsisch zellgängig zu machen, hängt von seiner Grçße, Ladung und Hydrophobie ab.E in Peptid kann einem passiven Penetrationsmechanismus unterliegen, wenn es eher klein ist -d efiniert durch ein Molekülvolumen < 1500 3 entsprechend einem Peptid von < 1100-1200 Dalton. CAPA ist nicht markierungsfrei und weist daher alle Probleme der markierungsbasierten Assays auf,w ie sie oben beschrieben wurden.…”
Section: Methoden Zur Messung Der Zellpenetrationunclassified
“…[171] HaloTag ist eine modifizierte Halogenalkan-Dehalogenase,die von Wood und Mitarbeitern entwickelt wurde und mit schneller Kinetik und hoher Selektivitätd urch Chloralkane markiert wird. [172,173] Bei CAPA werden Zellen zunächst mit dem zu untersuchenden, [125,[179][180][181][182] Die Entscheidung, wie ein Peptid zu modifizieren ist, um es intrinsisch zellgängig zu machen, hängt von seiner Grçße, Ladung und Hydrophobie ab.E in Peptid kann einem passiven Penetrationsmechanismus unterliegen, wenn es eher klein ist -d efiniert durch ein Molekülvolumen < 1500 3 entsprechend einem Peptid von < 1100-1200 Dalton. [65,135] Füre ine passive Zellpenetration ist auch die Zahl der solvensexponierten Wasserstoffbrückendonoren begrenzt.…”
Section: Methoden Zur Messung Der Zellpenetrationunclassified
See 2 more Smart Citations